Cultivation of Pleurotus Environtmental Friendly by Recycling Substrate Waste of Fungus and Organic Fertilizer Addition KULTIVASI JAMUR Pleurotus RAMAH LINGKUNGAN DENGAN MENDAUR ULANG LIMBAH SUBSTRAT JAMUR DAN PENAMBAHAN PUPUK ORGANIK - Elis Nina Herliyana; Mira Febrianti; Abdul Munif; Hanifah Nuryani Lioe (Jurnal Silvikultur Tropika, 2015)
White mushroom or Pleurotus ostreatus (Jacq:Fr) Kummer is one of wearthered wood that commonly found in nature. Some kinds of wood fungi, included white mushroom have been generally marketed in fresh form or in its cultivation such fungi chips. Substrate that commonly used for development of mushroom culture is saw powder of sengon wood. The more the cultivation of fungus and waste of the substrate is a lot of wasted, while its waste still has nutrition that can be recycled and reused for culturing mushroom, so that will be ecosystem friendly. The aim of this study is to learn about effect of application substrate waste of mushroom and addition of organic fertilizer on yield of white mushroom culture. Stages on this study are the making of substrate, spawning, maintenance and observation of fungus development, and analysis of chemical composition. Conducted observations are growth vegetative phase and reproductive phase, morphological character of body fruit, and result of chemical composition analysis of white mushroom body fruit. Medium composition 75% waste of mushroom substrate are mixed with 25% new substrate, showed the good growth and good yields. Addition of liquid organic fertilizer [0.2%] and [0.5%] gave the good yields. Moreover, medium and genetic factors, environmentral factor specially temperature and moisture really affected growth and the yields of white oyster mushroom.Key words: fungus culture, mushroom, Pleurotus, liquid organic fertilizer,